Catalytic Asymmetric Synthesis of syn Aldols with Methyl Ketone Functionality and anti Aldols with a Thioamide Group - Ota, Yuya; Li, Zhao; Kumagai, Naoya; Shibasaki, Masakatsu (Synlett, 2019)
Catalytic asymmetric syntheses of syn aldols with a methyl ketone functionality were studied to confirm the generality of the methodology. In addition, catalytic asymmetric synthesis of anti aldols with a thioamide group was carefully examined, giving the desired products, albeit with moderate diastereoselectivity.
Keywords: aldol reaction; catalytic asymmetric reaction; methyl ketone; thioamide